EXPLORING THE COMPLEX NARRATIVES OF TOXIC MASCULINITY ON THE INSTAGRAM ACCOUNT @Thegentlemanrising - Anwary, Aditia; Istiadah, Istiadah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This research delves into the intricate narratives surrounding toxic masculinity through a Multimodal Critical Discourse Analysis of content on the Instagram account Thegentlemanrising. The study investigates how ideas of toxic masculinity are represented in both visual and textual elements, specifically in photos and expressions shared on the platform. Thegentlemanrising actively communicates messages aimed at encouraging the younger generation to embrace masculinity, emphasizing positive attributes while avoiding toxic traits. The content consists of motivational quotes fostering a healthy masculine identity, often accompanied by images of individuals embodying positive masculine characteristics. This study positions Thegentlemanrising as an initiative to balance and juxtapose the concept of masculinity, promoting positive ideals and steering clear of toxic behaviors. The findings contribute to our understanding of how social media platforms can play a role in shaping discussions around masculinity and influencing perceptions among the audience, particularly the younger generation.